Siting charging stations and identifying safe and convenient routes for environmentally sustainable e-scooter systems - (:unkn) unknown (My University, 2022)
E-scooters are considered a new type of micromobility that promotes sustainable transportation modes by shifting the private car mode to a Mobility as a Service. Irregular parking and high life cycle global warming impacts of e-scooters due to dockless operating system cause a tendency from dockless systems to charging stations. This article presents one of the first comprehensive spatial analysis studies aiming to develop a novel GIS-based multi-criteria decision support model for: (1) siting optimum e-scooter charging station locations that will integrate e-scooter system with the existing public transportation systems and point of interests, and (2) finding the most secure and convenient road network to connect the charging stations. Identifying the optimum road network for connecting the charging stations and developing a raster based spatial method for this purpose distinguish this study from the previous studies. The developed model was implemented by performing a case study in Karsiyaka, Izmir, Turkey. 35 suitable locations were determined for siting e-scooter charging stations and the optimal connectivity network connecting each station with its neighboring stations were identified. The model can be reproduced for other locations and used to develop innovative policies and plans for environmentally more sustainable and operationally effective shared e-scooter systems.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; İnşaat Mühendisliği; Yapı; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Civil Engineering; Structure; Engineering and Technology; İNŞAAT VE YAPI TEKNOLOJİSİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENERJİ VE YAKITLAR; CONSTRUCTION & BUILDING TECHNOLOGY; ENGINEERING; Engineering, Computing & Technology (ENG); ENERGY & FUELS; Genel Mühendislik; Yapı ve inşaat; Mühendislik (çeşitli); Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fizik Bilimleri; General Engineering; Building and Construction; Engineering (miscellaneous); Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical Sciences; E -scooter; GIS analysis; Transportation planning; Site selection; Shared micromobility; Sustainable mobility; Multi -criteria decision making; Analytical hierarchy process; GIS